(untitled) (Research, Society and Development, 2021)
Introduction: The importance of knowledge and clarity of information on food labelling for allergic individuals. The purpose of this study is to contribute to explain the physiological mechanisms that trigger AA and to prevent allergy sufferers about labeling information in food acquisition, ensuring food safety and generating knowledge about inadequacies and health risks about food labelling for allergy sufferers, often caused by the difficulty of interpreting nutritional information contained in labels. The aim of the study was to analyze the knowledge and clarity of information on food labelling for AA pors. Methodology: This is an integrative literature review, which included observational studies, cohorts, conducted with people of both sexes and ethnicity, articles published in the period 2016-2021. Whose languages were in Portuguese or English with access to the full text. The search took place in the PubMed, Science Direct and LILACS databases, from May to June 2021 with the combinations of the following descriptors: Allergy, Food Labeling and Food. Results: Form identified in the PubMed search site (182) articles, science direct (226) and LILACS (3) articles. Of the articles found only 17, related to the importance and knowledge in the clarity of information on food labeling for allergy sufferers. Conclusion: The results of this integrative review verify that there are several flaws in the declarations for allergic at the same time a precaution in the labeling of allergens and labels that do not meet the resolution.